SPATIAL PLANNING IN BRASILIA: NEW DEMANDS, NEW SCALES, AND NEW APPROACHES - Farret, Ricardo (Revista Eletrônica: Tempo - Técnica - Território / Eletronic Magazine: Time - Technique - Territory, 2018)
Built a partir of a urbanistic basic plan, Brasília, the federal capital of Brazil, dedicated in 1960, with its rapid population growth and spatial occupation, sees the precocious emergence of a non-planned metropolitan structure. Only after the 1970s, even in a descontinuous way, is formulated various macro scales attempts to spatial planning: of the Federal District, of the Metropolitan Area, and of the Geoeconomic Region. In this article, the various spatial plans and projects proposed for the Federal District and its surrounding área are described in a resumed form.